An Fear a Phleasc - O Conghaile, Micheal,Bourke, Brian (Cló lar-Chonnacht, 1997)
(An Irish-language title) Powerful, artistic, articulate writing, apt and effective in exploring the type of material in question … if good short story writing was lagging in recent times this should awaken a crowd from their slumber! - Books Ireland A new world is created here by Micheal O Conghaile, a world which didn't and will never exist - but a world which is, nevertheless, uncannily familiar . . . stress, worry, irrationality and wit abound. Self identity and man's raison d'être explored.
Description based on publisher supplied metadata and other sources